2006
DOI: 10.1542/peds.2005-2318
|View full text |Cite
|
Sign up to set email alerts
|

Delaying Second Births Among Adolescent Mothers: A Randomized, Controlled Trial of a Home-Based Mentoring Program

Abstract: A home-based intervention founded on a mentorship model and targeted toward adolescent development, including negotiation skills, was effective in preventing rapid repeat births among low-income, black adolescent mothers. The effectiveness of the intervention could be seen after only 2 visits and increased over time. There were no second births among mothers who attended > or = 8 sessions. There was no evidence that risk behavior or contraceptive use was related to rapid second births. There was some evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 53 publications
1
123
1
Order By: Relevance
“…Social-cognitive-ecological theory 31 addresses cultural norms, modelling and the concepts of self-efficacy and support. It is based on Bandura's 32 postulation that a person's internalised standards for behaviour are developed from information conveyed by sources of social influence (parents, peers and characters portrayed in mass media) and their environment.…”
Section: Social-cognitive-ecological Theorymentioning
confidence: 99%
“…Social-cognitive-ecological theory 31 addresses cultural norms, modelling and the concepts of self-efficacy and support. It is based on Bandura's 32 postulation that a person's internalised standards for behaviour are developed from information conveyed by sources of social influence (parents, peers and characters portrayed in mass media) and their environment.…”
Section: Social-cognitive-ecological Theorymentioning
confidence: 99%
“…A randomized controlled trial of low-income black American adolescents participating in a home-based mentoring programme focusing on autonomy and parenting showed effectiveness as early as after two visits and the effect increased over time 82 . Having two or more intervention visits increased the odds of not having a second infant more than threefold.…”
Section: High-quality Studiesmentioning
confidence: 99%
“…Additionally, two studies reported no improvements in adolescent repeat pregnancies during the study periods (Barnet et al, 2007;Katz et al, 2011). On the other hand, two studies demonstrated success in reducing repeat adolescent pregnancies (Black et al, 2006;Koniak-Griffin et al, 2003). Of note, one study highlighted the impact of culture on the increased benefits from the program (Middlemiss & McGuigan, 2005).…”
Section: Community School and Home-based Interventions To Prevent Amentioning
confidence: 98%
“…Adverse factors may be past experiences with an unstable relationship with the baby's father, a history of abortion or adoption, a young maternal birth age, poverty, or poor school performance. Other adverse influences may include the adolescent's ambivalence, anxiety, depression, alcohol or drug use, social isolation, and a self-perceived violation of moral, religious, or cultural codes Black et al, 2006;Meade & Ickovics, 2005). In the presence of these factors, the adolescent mother is likely to be stuck in the recoil stage and may continue with familiar negative behaviors such as risky sexual practices, unintended repeat pregnancies, and eventually, school drop-out.…”
Section: Risk and Protective Factorsmentioning
confidence: 99%